1-a) cos(x) = -√3/2 ⇔ x= 5π/6 +2kπ ou x= -5π/6 + 2kπ
cos( 2x) = -√3/2 ⇔ 2x = 5π/6 +2kπ ou 2x = -5π/6+2kπ
⇔ x =(5π/6 + 2kπ)/2 ou x =(-5π/6 +2kπ)/2
⇔ x =5π12 +kπ ou x= -5π/12 + kπ
2- a) 2x³ + x² - x = 0 ⇔ x(2x² +x-1)=0
⇔ x =0 ou 2x² + x -1 =0
resoudre l'equation : 2x² + x -1 =0
Δ= 1² -4(2)(-1) = 1+8 = 9
-1+√9 -1 + 3 2 1
X1= ............... =.................=...... = .....
2×2 4 4 2
-1-√9 -1-3 -4
X2=................=............=.......... = - 1
2×2 4 4
les solutions de l'equation sont : 0 , -1 et 1/2
b) 2cos³( x) + cos²(x) - cos (x) = 0 ⇔ cos(x) [2cos²(x) +cos(x) -1] =0
⇔ cos(x) =0 ou 2cos²(x) +cos(x) -1 =0
⇔ cos(x) = 0 ou cos(x) = -1 ou cos(x) =1/2
cos(x) = 0 ⇔x= π/2 ou x=-π/2
cos(x) =-1 ⇔ x= π ou x =-π ( x= -π Rejeté solution)
cos(x) = 1/2 ⇔ x= π/3 ou x = -π/3
donc les solutions de l'equation sont : π/2 ,-π/2,π/3 ,-π/3 , π . .